Design and Structural Performance Evaluation of a Motorcycle Disc Brake Testing Device using Finite Element Method - Yana, I Nyoman Bramastra; Muthoriq, Ery; Gunawan, Gunawan; Hidayat, Dwi Wahyu (Jurnal Rekayasa Mesin, 2026)
The increasing demand for reliable motorcycle braking systems requires accurate performance evaluation under controlled conditions, where a brake testing device plays an important role and its structural integrity becomes a key factor in ensuring safe and stable operation. The design and structural evaluation of a motorcycle disc brake testing device are conducted using the Finite Element Method (FEM), focusing on the main components including the frame, load actuator, and load holder under static loading conditions. The structure is constructed using ASTM A36 steel to provide adequate strength and stiffness, while mechanical components such as the electric motor, brake disc, and shaft are simplified as equivalent loads to reduce computational complexity without compromising realistic working conditions. The simulation results show that the maximum von Mises stresses on the frame, load actuator, and load holder are 42.92 MPa, 56.02 MPa, and 68.18 MPa, respectively, which are below the material yield strength of 250 MPa, with maximum displacements within acceptable limits and safety factors greater than 3, indicating that the structure is safe and reliable for operation.